Labeling of Genetically Modified (GM) Foods in Peru: Current Dogma and Insights of the Regulatory and Legal Statutes. (12th May 2022) - Delgado-Zegarra, Jaime; Alvarez-Risco, Aldo; Cárdenas, Carmen; Donoso, Massiel; Moscoso, Stephanie; Rojas Román, Brenda; Del-Aguila-Arcentales, Shyla; Davies, Neal M.; Yáñez, Jaime A.
Abstract : The COVID-19 pandemic has affected and afflicted human lives and been a transformative catalyst leading to closure of many companies, disrupting mental health, and reducing access to food and exacerbating food insecurity. This presents an opportunity to reflect on and examine genetically modified (GM) foods and their effective legislative regulation for the benefit of consumers. This review presents a detailed analysis of GM foods' regulation in Peru and the analysis of certain specific cases that show the need for greater regulation of the industry.